Stability of reinforcements (CrB2/TiB2) and lubricants (C/MoS2) in Cu matrix during the sintering process - Chen Zhang; Lei Jia; Jia-mei Zhang; Wu Pan; Zhen-lin Lu; Zhi-guo Xing (Journal of Materials Research and Technology)
To select suitable reinforcement and lubricant for Cu matrix and thus improve the tribological performance, the stability of widely used reinforcements and lubricants, such as CrB2, TiB2, graphite (C) and MoS2, in the copper matrix during sintering process was studied. The content of each reinforcement or lubricant was fixed at 10 wt%, and the powder mixture was sintered by a fast hot-pressed sintering machine at 950 °C under 40 MPa for 1 h under a vacuum atmosphere (<10 Pa). Then, microstructure and phase composition of the composites resulted from 10%CrB2–Cu, 10%TiB2–Cu, 10%MoS2–Cu, 10%C–Cu, 10%CrB2–10%C–Cu, 10%TiB2–10%C–Cu, 10%CrB2–10%MoS2–Cu and 10%TiB2–10%MoS2–Cu powder systems were investigated systematically, Subsequently, the potential decomposition and reaction behavior was discussed based thermodynamic analysis. Results show that single CrB2, TiB2 or C phase can exist stably in copper matrix, but MoS2 is prone to react with Cu to form Cu2S and Mo2S3. Both CrB2 and TiB2 can co-exist with C in the Cu matrix, but react with MoS2 to form Cu2S, Mo2S3 as well as ternary CuCrS2 and CuTi2S4 phase, since the negative Gibbs free energy change of the corresponding reaction equations. Finally, the strengthening effect of CrB2 and TiB2 along with the lubricating effect of graphite (C) are promise to work in Cu matrix from the viewpoint of crystal structure integrity.